The Influence of the Direct Instruction Learning Model on Student Learning Outcomes in Elementary Schools - Yose Stedy; Daniel Alfanta (Journal of Education Innovation and Curriculum Development, 2024)
This research investigates the influence of the Direct Instruction (DI) learning model on student learning outcomes in elementary schools. Direct Instruction, characterized by its structured, explicit, and teacher-centered approach, has been widely recognized for improving academic performance, particularly in foundational subjects. Using a quasi-experimental design, this study compared the learning outcomes of students taught through DI with those taught using conventional instructional methods. Results showed that students exposed to DI demonstrated significantly higher academic achievements compared to their peers in the control group. The findings align with existing research highlighting the effectiveness of DI in enhancing student mastery of content and reducing learning gaps. However, the study also acknowledges limitations, including sample size, implementation fidelity, and external influences on student performance. These results suggest that with proper training and adaptation, DI can serve as a valuable instructional strategy to boost student achievement in elementary education. Future research is recommended to explore long-term impacts and broader application across diverse educational settings.